Influence of carcass chilling time on the progression of rigor mortis, carcass characteristics and physicochemical properties related to the colour and tenderness of longissimus thoracis et lumborum and biceps femoris muscles in Botucatu rabbits - Dutra, Daniel Rodrigues [UNESP] (2025)
The objective of this study was to characterize the progression of rigor mortis and evaluate the influence of chilling time on carcass characteristics, colour, and tenderness of Botucatu rabbit meat in both males and females. The muscles analyzed were the longissimus thoracis et lumborum (LTL) and biceps femoris (BF). As chilling time progressed, weight loss due to chilling increased (P < 0.001), whereas weight loss due to thawing (P = 0.035) and volume of exudate post-thawing (P = 0.022) decreased. Cold carcass yield remained stable for 18 h of chilling, with greater (P < 0.001) values for males. The colour parameters L*, a* and b* were significantly influenced by sex and chilling time. Rigor mortis began at 1.5 h post-mortem, was established between 4.5 and 6 h, and resolved at 18 h of chilling. Biceps femoris showed greater (P < 0.001) shear force at 0 h and 4.5 h, with reduced (P < 0.001) tenderness in males compared to females. Sarcomere length was shorter (P < 0.001) at 24 h in BF and from 18 h in LTL. Myofibrillar fragmentation index of both muscles, and water holding capacity of BF increased (P < 0.001) with chilling time. Therefore, it is concluded that chilling the carcasses for 18 h prior to freezing results in reduced weight losses, increased luminosity and tenderness of Botucatu rabbit meat.